HUBUNGAN MEDIA TERHADAP PERILAKU BULLIYING DI SMA SEDERAJAT KECAMATAN PARE KEDIRI - Nadiah Nadiah; Maria Ulfah; Kunaenih Kunaenih (Almarhalah, 2022)
AbstractThe development of information technology brings a change in society, the birth of the media itself makes people's behavior patterns experience a shift in both culture, ethics and existing norms. In fact, the internet has now become a necessary necessity for the majority in many circles, with the development of the media so that it has an impact, one of the impacts is that many teenagers are bullying others in verbal and non-verbal forms. The purpose of this study is to find out how related the media is so that it can trigger bullying behavior. The method used in this study is descriptive analytical correlation. And the results of this study are the relationship between social media and bullying behavior. If it is seen that the rxy obtained is 0.665, it turns out that it lies between 0.40 - 0.70 based on the guidelines contained in the table. So it can be stated that the correlation between the variables X and Y is a moderate or sufficient correlation. Keywords: Media, Bulliying, Verbal